2015
DOI: 10.3892/ijo.2015.2906
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine inhibits human rhabdomyosarcoma cell growth by downregulating insulin-like growth factor 2 expression and reactivating the H19 gene product miR-675, which negatively affects insulin-like growth factors and insulin signaling

Abstract: Abstract. insulin-like growth factor 2 (igf2) and 1 (igf1) and insulin (inS) promote proliferation of rhabdomyosarcoma (rMS) cells by interacting with the insulin-like growth factor 1 receptor (igf1r) and the insulin receptor (inSr). loss of imprinting (loi) by Dna hypermethylation at the differentially methylated region (DMr) for the igf2-H19 locus is commonly observed in rMS cells and results in an increase in the expression of proliferation-promoting igf2 and downregulation of proliferation-inhibiting non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
1
20
0
1
Order By: Relevance
“…Since the maternal ICR in IGF2 gene is not methylated and as a consequence of 5-azacytidine treatment, ICR on the paternal IGF2 becomes hypomethylated and IGF2 expression from the paternal gene would be strongly inhibited [149]. In line with this, 5azacytidine treatment inhibited rhabdomyosarcoma cell growth through repression of IGF2 expression and re-expression of H19 in vitro [150]. Additionally, it has been shown that IGF2 can maintain cancer stem cell populations in breast cancer [151] and HCC [152].…”
Section: Igf2 Targeting In Cancer and Therapy Resistancementioning
confidence: 90%
“…Since the maternal ICR in IGF2 gene is not methylated and as a consequence of 5-azacytidine treatment, ICR on the paternal IGF2 becomes hypomethylated and IGF2 expression from the paternal gene would be strongly inhibited [149]. In line with this, 5azacytidine treatment inhibited rhabdomyosarcoma cell growth through repression of IGF2 expression and re-expression of H19 in vitro [150]. Additionally, it has been shown that IGF2 can maintain cancer stem cell populations in breast cancer [151] and HCC [152].…”
Section: Igf2 Targeting In Cancer and Therapy Resistancementioning
confidence: 90%
“…Because paternally expressed imprinted genes (Igf2 and Rasgrf1) enhance embryonic growth, and maternally expressed genes (H19, p57 KIP2 , and Igf2r) inhibit cell proliferation, the unique genomic imprinting pattern observed in VSELs demonstrates the growth-repressive influence of imprinted genes, including the Igf2-H19 locus, on the proliferation of these cells. One miRNA derived from the H19 ncRNA has been demonstrated to inhibit expression of the signaling receptor for Igf2, the insulin-like growth factor 1 receptor (Igf1r) (8), and in addition we have proposed the same phenomenon for the insulin receptor itself (17). Therefore, VSELs are in a quiescent state because of attenuation of insulin/insulinlike growth factor signaling (18,19).…”
Section: Igf2-h19 Locus As Master Regulator Of Hscs Fatementioning
confidence: 92%
“…The expression of IGF1R, InsR in RMS cell lines was evaluated by flow cytometry as previously described [ 24 ]. Briefly, the receptor expression was assayed with phycoerythrin (PE)-anti-IGF1R monoclonal antibody Clone 33,255 and anti–human/mouse Insulin R/CD220 conjugated with APC (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%